Dochody powiatów ziemskich na jednego mieszkańca - przekrój regionalny - Bury, Agata (The Poviats' Revenues Per Capita - by Voivodeships, 2008)
There are two types of poviats in Poland: 314 "regular" poviats and 65 cities with poviat status. The paper presents the "regular" poviats' revenues per capita. It contains the analysis of this index, in every poviat between 2002 and 2005. Poviats have various indexes. The highest indexes have been noticed in two voivodships of eastern Poland: podkarpackie and warmińsko-mazurskie, and also in voivodships which are traditionally recognized as the richest one: mazowieckie and wielkopolskie. There are the poorest poviats in the vicinity of cities with poviat status. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 507-518